Analisis Pengaruh Religiusitas Terhadap Etika Penggelapan Pajak (Studi Kasus pada Wajib Pajak di Kabupaten Karanganyar) - Ababil, Yunita; Harimurti, Fadjar (Teewan Journal Solutions, 2025)
Tax evasion is the act of minimizing the tax owed by violating tax laws and regulations carried out by taxpayers. This research aims to analyze the influence of intrapersonal religiosity and interpersonal religiosity on the ethics of tax evasion. This research uses theory, namely attribution theory. The objects of this research are people who have become taxpayers in Karanganyar Regency. The number of samples in this study was 89 samples. The sampling technique uses the Simple Random Sampling technique. The type of data used in this research is primary data. The data collection technique in this research used a questionnaire. The data analysis techniques in this research are multiple linear regression analysis, t test, f test, and coefficient of determination. The results show that intrapersonal religiosity has a significant positive effect on the ethics of tax evasion, and interpersonal religiosity has no significant negative effect on the ethics of tax evasion.